Dendritic Cell-Targeted Vaccines - Cohn, Lillian; Delamarre, Lélia (Frontiers in Immunology, 2014)
Despite significant effort, the development of effective vaccines inducing strong and durable T cell responses against intracellular pathogens and cancer cells has remained a challenge. The initiation of effector CD8+ T cell responses requires the presentation of peptides derived from internalized antigen on class I MHC molecules by dendritic cells (DCs) in a process called cross-presentation. A current strategy to enhance the effectiveness of vaccination is to deliver antigens directly to DCs. This is done via selective targeting of antigen using monoclonal antibodies directed against endocytic receptors on the surface of the DCs. In this review we will discuss considerations relevant to the design of such vaccines: the existence of DC subsets with specialized functions, the impact of the antigen intracellular trafficking on cross-presentation, and the influence of maturation signals received by DCs on the outcome of the immune response.